Integrated Groundwater Management 2016
DOI: 10.1007/978-3-319-23576-9_23
|View full text |Cite
|
Sign up to set email alerts
|

Liberation or Anarchy? The Janus Nature of Groundwater Use on North Africa’s New Irrigation Frontiers

Abstract: Two contrasting views prevail on groundwater use in situations of predominantly state-led irrigation development. The first considers 'groundwater as liberation', i.e., how, by capturing the irrigation initiative, farmers liberated themselves from 'state' water, enabling more intensive and productive agriculture. The second view -'groundwater as anarchy' -considers groundwater as a M. Kuper (*) Cirad,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
0
24
0
8
Order By: Relevance
“…In semi-arid contexts, sustainable water use has to be promoted, given the ongoing trend of groundwater depletion (Wada et al, 2012). In the case of Morocco, increased pressure on groundwater is already threatening the sustainability of many farming systems that depend on it (Kuper et al, 2015). The main objective of this study therefore consists of estimating the water footprint of cattle products (milk and live weight gain) in dual-purpose herds by considering the volumes of water used and their origins: rainfall, irrigation (whether from surface water or groundwater) and virtual water.…”
Section: Introductionmentioning
confidence: 99%
“…In semi-arid contexts, sustainable water use has to be promoted, given the ongoing trend of groundwater depletion (Wada et al, 2012). In the case of Morocco, increased pressure on groundwater is already threatening the sustainability of many farming systems that depend on it (Kuper et al, 2015). The main objective of this study therefore consists of estimating the water footprint of cattle products (milk and live weight gain) in dual-purpose herds by considering the volumes of water used and their origins: rainfall, irrigation (whether from surface water or groundwater) and virtual water.…”
Section: Introductionmentioning
confidence: 99%
“…Though the risks of overexploitation of the deep aquifer are known, the stakeholders do not seem to be able to act effectively in a coordinated manner for sustainable management in the current context. Such situations are unfortunately rather common in North Africa (Kuper et al, ) and worldwide. Many studies have shown that resorting to groundwater is a common response of farmers to water scarcity (Tyagi et al, ; Molle et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kuper et al (2016), groundwater supplies more than 500,000 farms in Algeria, Morocco and Tunisia and pumping wells irrigate continuously growing areas now estimated at more than 1.75 million ha. Such an economic development strategy largely relies on groundwater resources that have been prone to severe depletion since the start of their intensive exploitation nearly 40 years ago.…”
Section: Introductionmentioning
confidence: 99%